Stakeholders’ Engagement and School Performance: Basis for a Proposed School-Community Partnership Program - Sison, Marilyn N.; Fuentes, Helen C. (Future Science / FSH-PH Publications, 2025)
This study investigated the relationship between stakeholders' en-gagement and school performance, focusing on elementary schools in the Schools Division of Borongan City. The specific objectives were to determine the extent of stakeholder involvement in instructional, physical, and values development; evaluate the performance of re-spondent schools in terms of student achievement, school awards and recognition, and School-Based Management (SBM) level of prac-tice. Utilizing a descriptive-correlational research design, data were gathered through survey questionnaires adapted and analyzed the prevailing conditions and cause-effect relationships. The study in-volved elementary school heads and SBM coordinators, who were selected via purposive sampling through total enumeration. Findings indicated active stakeholder engagement across instructional, physi-cal, and values development areas. Among the 40 respondent schools, 47.5% were classified as very satisfactory and 52.5% as satisfactory in student achievement. Additionally, 50% of schools excelled in awards and recognition, 45% were moderately performing, and 5% were not performing. At the SBM level of practice, 95% were classi-fied as progressive, with only 5% at the mature level. Statistical anal-ysis revealed that student achievement and SBM level of practice were not significantly related to stakeholder engagement, with p-values of .315 and .715, respectively. However, a significant relation-ship was found between stakeholder engagement and school awards and recognition, with a p-value of .045. These results underscore the importance of stakeholder engagement in enhancing certain aspects of school performance, particularly in achieving awards and recogni-tion, highlighting areas where further improvements and strategies are needed to link engagement more directly with academic out-comes and SBM practices.